DEVELOPMENT OF A SOFTWARE MODULE FOR CENTRALIZED THE CONTROL CONTAINS DATA FOR PROGRAM COMPLEX "GEOPOISK" - Зацерковний, В. І.; Халімендік, В. В. (Science-based technologies, 2016)
Any technological process, including technology of software development is a complex process that depends on the choice of structural model of the future software. In this work was made analysis and determined that the structure of the software package "GeoPoisk", which is made up of more than 30 applications, is a symbiosis between two model "every problem — a separate program" and modular. Following the analysis, it was developed method to solve problem of centralized management of geodatabase data and its objects, which involved in different modules “GeoPoisk”. The method is based on safekeeping, by writing to the INI-file, database configuration properties, such as information about the number of fields, group of drills and number of drill hole, which will be active to use. Also developed software module "manager" for automated solution to this problem. The program implements the following list of interactions: with the launch of control program, load from INI-file the last saved configuration, with any change in the control program is replacing the old configuration to the new, when launch a new module of "GeoPoisk" it gets working configuration from INI-file. This greatly facilitates the use of the software package "GeoPoisk" because there is no need to tune on the configuration to those, which used in previous modules, each time, when launch another module of "GeoPoisk". This is very useful when working with basic modules of "GeoPoisk": geodatabase explorer , tablets, geophysical formulas language.